Factors Affecting Internet Literacy of Smallholder Cocoa Farmers in Aceh, Indonesia - Elvira Iskandar, Siti Amanah, Aida Vitayala S. Hubeis, Dwi Sadono (International Journal of Advanced Science and Technology, 2020)
The recent development of Information and Communication Technology (ICT) encourages the use of the internet as a source of information for cocoa farmers. The farmers need innovation and technology to improve the quality of cocoa production. This study was aimed to analyze the factors influencing farmers’ internet literacy. A survey was conducted in Pidie Jaya and Southeast Aceh. Random sampling techniques were used to select 352 cocoa farmers as research respondents. The independent variables used were farmers’ age, education level, number of dependents, farming experiences and cultivated land area, while dependent variable was farmers’ internet literacy rate. The effect of independent variables to dependent variable were analyzed by regression analysis using SPSS. The results revealed that farmers had a very low rate of internet literacy. There was limited ownership of communication facilities and intensity of internet utilization, while the application of information derived from the internet for farming was very low. Education level was found to have a positive and significant effect on farmers’ internet literacy rate, whereas the age of farmer and farming experiences showed a significantly negative effect. Farmers were lack of ability to select and apply information obtained from the internet independently, hence interpersonal communication with extension agents was still prominent for the farmers. The effort to increase farmers’ internet literacy can be done through strengthening farmers ability in utilizing internet through extension services and institutional support. Keywords: cocoa smallholders, information technology, internet literacy